Basic concepts literary genre "romance"in the context of origin (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The paper proposes a theoretical and literary history of the concept of genre features of the novel in the context of their development, starting with the ancient literature of the first half of the twentieth century. Much attention is paid to the theoretical writings, which are fundamental to the poetics and typology novelistic genre.
Keywords: novel; genre; epics; the greek novel; romance; russian novel